2003
DOI: 10.1002/cbf.1024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeic acid phenethyl ester and alpha‐tocopherol on reperfusion injury in rat brain

Abstract: Oxygen-derived free radicals have been implicated in the pathogenesis of cerebral injury after ischaemia-reperfusion. Caffeic acid phenethyl ester (CAPE), an active component of propolis extract, exhibits antioxidant properties. The purpose of the present study was to investigate the effects of ischaemia and subsequent reperfusion on rat brain and to investigate the effects of two free radical scavengers, CAPE and alpha-tocopherol, on this in vivo model of cerebral injury. Ischaemia was induced by bilateral oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 43 publications
10
61
1
2
Order By: Relevance
“…In the present study, levels of MDA, antioxidant enzymes (SOD and GSH-Px) and GSH of blood and some organs were found similar in the groups. It can be speculated that there was no correlation of antioxidant enzyme activities between tissues (Irmak et al 2003). Similarly, Okutan et al (2005) reported that there is no consensus in the level of antioxidant enzymes of many organs in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, levels of MDA, antioxidant enzymes (SOD and GSH-Px) and GSH of blood and some organs were found similar in the groups. It can be speculated that there was no correlation of antioxidant enzyme activities between tissues (Irmak et al 2003). Similarly, Okutan et al (2005) reported that there is no consensus in the level of antioxidant enzymes of many organs in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated to be a specific inhibitor of activation of nuclear transcript factor NF-B (2,3). Previous studies have shown that this compound could protect the spinal cord and brain from ischemia reperfusion injury (4,5) and prevent neurotoxic events caused by excessive inflammatory reaction in brain (6). Several lines of evidence also indicate that CAPE may modify the redox state in transformed fibroblast cells and in leukemic HL-60 cells (7)(8)(9).…”
Section: Caffeic Acid Phenethyl Ester (Cape)mentioning
confidence: 99%
“…ROS involve free radicals that contain one or more unpaired electrons. ROS-induced oxidative stress has been implicated in variously pathological conditions: cancer, diabetes, ischemia/reperfusion, aging and neuropsychiatric disorders (Lohr, 1991;Sayre et al, 2001;Irmak et al, 2003;Jenner, 2003;Dalle-Donne et al, 2006). Accumulation of ROS induces oxidative damage, which involves cellular proteins, lipids, nucleic acids and DNA after an ischemic insult, which leads to neuronal death (Radi et al, 1993;Giulivi et al, 1995).…”
Section: Introductionmentioning
confidence: 99%